ChemInform Abstract: A Complementary Route to Diaminopyrimidines Through Regioselective SNAr Amination Reactions. Issue 27 (18th June 2015) - O'Donnell, Michael; Charrier, Jean‐Damien
Abstract 2‐Chloro‐4‐(2, 3, 5, 6‐tetrafluorophenoxy)pyrimidine (I) can be diaminated in a regioselective stepwise manner: first amination occurs at C‐2, second amination at C‐4.